Reuse of gypsum waste in the execution of internal coating of partition walls - Schmitz, Ítalo Benjamin (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
Gypsum is being used on a large scale as internal wall coating because it is a low-cost and high-performance material. However, a large amount of waste is generated in this process, which is an economic and environmental problem. Although there seems to be growing interest in the use of this type of waste as coatings for internal walls, very little is known about its production technology and behavior. The aim of this research study is to investigate the performance of this material by using surface hardness, compressive strength and adhesion tests, as well as to describe the use of gypsum waste in this coating technique. Those tests were carried out using mixes with 0%, 5% and 10% waste with 0.6 mm maximum diameter. Also, technical visits to building sites were undertaken in order to assess and determine the most appropriate coating technique. The results indicated that the addition of waste does not worsen the properties investigated, and up to 10% of gypsum waste is admissible in the production of new plaster, in conformity with building technique recommendations.